(Re)shaping ethical considerations in involuntary admission for inpatient psychiatric care: An empirical ethics inquiry drawing insights from a South African case study - Wickremsinhe, M (2021)
Involuntary admission for inpatient psychiatric care, though common in clinical practice, remains a long-standing ethical challenge in mental healthcare. Continued disagreement over when, if ever, involuntary admission can be ethically justified (in the psychiatric ethics literature) sits against the backdrop of calls for increased access to mental healthcare in low- and middle-income countries (in the global mental health discourse). My thesis takes this normative tension as a starting point for inquiry. I first review scholarship in psychiatric ethics and global mental health to identify ethical principles relevant to involuntary admission. I argue that the principles identified diverge along normative ideologies: psychiatric ethics is rooted in a negative rights framework while global mental health is rooted in a positive entitlements framework. In light of this divergence, I adopt an empirical ethics approach to 1) explore the normative commitments that do impact decision-making for involuntary admission in practice—drawing insights from a South African case study—in order to 2) understand the normative commitments that should impact decision-making for involuntary admission in practice. Using semi-structured interviews with mental healthcare practitioners and mental health advocates, my empirical data analysis demonstrates that practitioners’ decisions are influenced by a number of extra-legal considerations. These considerations focus not only on the individual being assessed, but also on their family availability, facility-based and broader resource constraints, and the health system structure. I focus my ethical analysis on the normative value of incorporating resource- and system-focused considerations in decision-making, especially given their relevance to the provision of mental healthcare in low- and middle-income country contexts. I argue that resource-focused considerations—though essential to the proper application of a positive entitlements framework—should not be incorporated into decision-making for involuntary admission, while system-focused considerations should—in order to better meet the demands of a negative rights framework. My work offers a novel contribution to the ‘intractable’ debate over the ethics of involuntary admission by demonstrating that dominant ethical principles invoked in both psychiatric ethics and global mental health do not fully capture the range of considerations that should be taken into account in decision-making in practice.